Material didáctico para el desarrollo de las destrezas con criterios de desempeño del bloque curricular numérico, módulo 6 del área de Matemática, con los estudiantes del quinto grado de educación general básica de la escuela Miguel Riofrío Nro. 2, de la ciudad de Loja. Período 2014-2015 - Suquilanda Elizalde, Luisana del Cisne (2015)
The research titled TEACHING MATERIALS FOR DEVELOPING SKILLS WITH PERFORMANCE CRITERIA BLOCK NUMBER CURRICULUM, MODULE 6 MATHEMATICS AREA WITH FIFTH GRADE STUDENTS OF BASIC EDUCATION GENERAL MIGUEL SCHOOL Riofrio NRO. 2 OF Loja. PERIOD 2014-2015, had as general objective to apply the specific teaching materials to develop skills with performance criteria in the area of mathematics students in the fifth grade of General Basic Education School No.2 Miguel Riofrio Research was type pre-experimental, transversal, descriptive and field for this the inductive, deductive and observational methods, techniques such as survey and signing with their instruments and the questionnaire was used index cards. In the research process involving a teacher and twenty-three fifth graders. After the analysis and interpretation of data it is determined that the teacher does not produce concrete material for the development of math classes which creates a traditional atmosphere, involving the student in mechanical processes that do not allow you to generate significant learning necessary for troubleshooting of everyday life. It is concluded that the use of specific teaching materials is essential to improve student learning